Evaluation of the first oral rabies vaccination campaign of the red foxes in Greece. Issue 1 (2nd January 2016) - Korou, Laskarina-Maria; Tasioudi, Konstantia E.; Tzani, Myrsini; Konstantinidis, Athanasios; Plevraki, Aikaterini; Iliadou, Peristera; Kostoglou, Petroula; Kaimaras, Dimitrios; Doudounakis, Spyridon; Mangana-Vougiouka, Olga
Abstract: Following the late 2012 recurrence of rabies in wild foxes ( Vulpes vulpes ) in central and north-western Greece, the first oral fox vaccination campaign co-financed by the European Union (EU) and the Greek state budget, was implemented. Initially, it involved 24 regional units of the Greek territory during the period October–December 2013. Vaccine-baits were aerially distributed by fixed-wing aircrafts. Vaccines were scattered along parallel flight paths 500 m apart in order to optimize aerial missions and achieve homogeneous distribution. A geographical information system was used to objectively evaluate bait distribution. This system identified areas of inadequate bait density that would require additional flights. A total number of 1, 504, 821 baits were distributed covering an area of 54, 584.29 km 2 . To assess the effectiveness of oral vaccination campaign a monitoring program was introduced, which entailed examination of serum samples and canine teeth derived from red foxes collected in the field. The laboratory analysis revealed 60% seropositivity and detection of tetracycline biomarker in 70% of the foxes tested.